Household Biomass Gas Stove Performance and Exhaust Gas Emission - Jansri, S N; Kumpanalaisatit, M; Sataklang, T (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
This work focuses on the design of the household biomass gas stove which is suitable for the lifestyle of the Thai northern people. In addition, the performance and exhaust emission of the stove - updraft gasifier - was design per the community requirement were evaluated. The stove consists of a combustion chamber – a primary chamber - and a secondary chamber with the primary and secondary air inlet of 0.016 and 0.002 m2, respectively. Moreover, the flow rate of primary air and secondary air was 0.456 and 1.340 kg/s, respectively. The performance of the stove was analyzed by the water boiling test technique and the emission of exhaust gas was evaluated with a fuel gas analyzer. The result indicated that the thermal efficiency of the stove was 44.84%. The specific fuel consumption was 0.029 kg/kg of water. Comparing the designed stove with the traditional clay brazier stove, the performance of the designed stove was higher than the traditional stove. The emission comparison between the designed household biomass gas stove, the traditional stove and the Thai exhaust gas emission standard indicated that both stoves released NOx and SO2 which are less than the standard whereas CO emission of the designed stove conformed to the standard. This work confirmed that the efficiency and the exhaust gas emission of the designed stove are better than the traditional stove. Therefore, this household biomass gas stove could replace the conventional stove